2012
DOI: 10.1186/1753-2000-6-27
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of identity development and identity diffusion in adolescence - Theoretical basis and psychometric properties of the self-report questionnaire AIDA

Abstract: BackgroundIn the continuing revision of Diagnostic and Statistical Manual (DSM-V) “identity” is integrated as a central diagnostic criterion for personality disorders (self-related personality functioning). According to Kernberg, identity diffusion is one of the core elements of borderline personality organization. As there is no elaborated self-rating inventory to assess identity development in healthy and disturbed adolescents, we developed the AIDA (Assessment of Identity Development in Adolescence) questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
157
0
13

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(191 citation statements)
references
References 45 publications
(60 reference statements)
14
157
0
13
Order By: Relevance
“…First, with regard to diagnosis and assessment of personality disorder in adolescents, future research should incorporate a staging theory of BPD distinguishing early precursors and early manifestations of BPD symptoms, including developmentally adapted criteria for young and older adolescents [141]. Diagnosis of BPD should also integrate dimensional factors (as identified in factor analytic studies) alongside categorical DSM/ICD diagnostic criteria, including further research on the promising alternative model for personality disorders presented in Section III of DSM-5 [12, p. 761], which emphasizes impairments in self and relatedness as dimensional core features of personality disorders.…”
Section: Discussionmentioning
confidence: 99%
“…First, with regard to diagnosis and assessment of personality disorder in adolescents, future research should incorporate a staging theory of BPD distinguishing early precursors and early manifestations of BPD symptoms, including developmentally adapted criteria for young and older adolescents [141]. Diagnosis of BPD should also integrate dimensional factors (as identified in factor analytic studies) alongside categorical DSM/ICD diagnostic criteria, including further research on the promising alternative model for personality disorders presented in Section III of DSM-5 [12, p. 761], which emphasizes impairments in self and relatedness as dimensional core features of personality disorders.…”
Section: Discussionmentioning
confidence: 99%
“…This lack of certainty can result in the creation of a false self, a protective mask meant to diffuse the discrepancy between the adolescents' perceptions of who they are as opposed to how they believe they are perceived by other important people (Broughton, 1981;Dayton, 2009;Goth et al, 2012;Kernberg, 1985). The false self may initially be used to ward off anxiety or feelings of inferiority, but in some instances can become so well accepted that it is compulsive and unconscious as the adolescent loses sight of rectifying the discrepancies between the false and true selves (Dayton, 2009;Sartain, North, Strange, & Chapman, 1973).…”
Section: Impacts Of Technology Use On Youth Mental Healthmentioning
confidence: 99%
“…The mean of participants' age was 15.42 years, standard deviation -0.871. Participants were asked to fill questionnaire consisting of sociodemographic questions, Goth, Foelsch et al (2012) The results of this study had shown that adolescents identity diffusion interface positively with conflict behaviour with their parents, and negatively with adolescent's differentiation of self and satisfaction with life. There were also founded that differentiation of self and satisfaction of life mediate relationship between adolescents' conflict behaviour with parents and identity diffusion.…”
Section: Discussionmentioning
confidence: 98%
“…Pagal M. Boweno (1978) šeimos sistemų teoriją savidiferenciacijos procesas vyksta asmenybės raidos metu, kai asmuo išsiugdo unikalų savasties jausmą (tai būtų panašu su identiteto koncepcija), suvokia save kaip atskirą asmenybę ir išmoksta atskirti ir išlaikyti pusiausvyrą tarp savo mąstymo ir jausmų. Tai siejasi su paauglio identiteto integracija (teigiamai išspręsta krize, pasiektu identitetu), kuri, remiantis E. H. Eriksono (1968) teorija, gali būti apibūdinama tokiais aspektais kaip savo asmenybės pastovumo, autonomiškumo, savo bruožų, mąstymo ir jausmų suvokimas (Goth et al, 2012). M. Bowenas (1978) teigė, kad savidiferenciacijos lygis yra perduodamas iš kartos į kartą, tėvų vaikams multigeneracinio proceso metu.…”
Section: Issn 1392-639x E-issn 2351-6585unclassified